محددات السياسة الائتمانية للبنوك التجارية الجزائرية دراسة تحليلية للفترة (2009-1989) - القري, عبد الرحمان; عبادي, محمد (جامعة الوادي - University of Eloued, 2017)
هدفت الدراسة إلى تحليل محددات السياسة الائتمانية للبنوك العاملة في الجزائر للفترة (2009-1989)، باستخدام بيانات سنوية. وقد قامت الدراسة بتحليل أربع متغيرات هي الائتمان المحلي، إجمالي الودائع، هامش سعر الفائدة ومعدل البطالة، باستخدام متغير وسيط ممثلا في الناتج المحلي الإجمالي. توصلت الدراسة إلى فعالية تأثير كل من الائتمان المصرفي وإجمالي الودائع ومعدل البطالة بصفة أساسية، وتأثير ضعيف لهامش سعر الفائدة نظر لتدخل السلطات النقدية للتحكم بها وتغييرها Abstract : The study aimed to analyze the determinants of the credit policy of Algerian Commercial Banks for the period (2009-1989), using annual data. The study analyzed four variables: Domestic credit, Total Deposits, Spread Interest Rate, and the unemployment rate using an intermediate variable represented by the gross domestic product. The Study found the effectiveness of the effect of Domestic Credit and total deposits and the unemployment rate mainly, and a little effect of the Spread interest rate because of the intervention of monetary authorities to control and change it
Determinants of Credit Policy of Algerian Commercial Banks Analytical Study for the period (2009-1989)
مقال بمجلة الدراسات المالية والمحاسبية . مج 08 ع01. جوان 2017 . جامعة الوادي
Keywords: السياسة الائتمانية، الائتمان المصرفي، إجمالي الودائع، معدل البطالة، البنوك التجارية الجزائرية